Analisis Kelayakan Usaha Peternakan Ayam Petelur di Kecamatan Mantup Kabupaten Lamongan - Moh Jaenal Ikhwan; Parikesit Penansang (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
The purpose of this study is to examine the profitability, income, and viability of laying hen farms in Lamongan Regency's Mantup District. Lamongan Regency's Mantup District. There were six informants who owned laying hen farms for this research. In this study, total costs, revenues, income, and business viability were the data analysis types used. The average total cost from six informants of IDR 755,812,161/Production Period is the result of this study. IDR 1,581,968,000 is the average revenue received per production period. During the production period, the average income obtained was IDR 826,155,833. Six laying hen breeder informants in Mantup District, Lamongan Regency, had their three business feasibility metrics calculated. The average R/C ratio value was 2.07, the average B/C ratio was 1.07, and the average ROI value was 92.50%. Therefore, it is viable to operate and grow the laying chicken farming company in Mantup District, Lamongan Regency, according to the calculation results.